Efecto del covid-19 y su incidencia financiera en las exportaciones del sector cacaotero. - Mena Coronel, Karla Cristina (My University, 2021)
This research analyzes the incidence of the health emergency on the level of exports in the country's cocoa sector, during the year 2020 in relation to previous periods, by searching and collecting information in different statistical sources in the country. Ecuador is considered one of the main exporters of fine aroma cocoa, for which it has a good reputation and recognition in the international market. On the other hand, Covid-19 affected all economic activities worldwide, for this reason, through a qualitative methodology, a bibliographic review and data analysis was carried out to identify the effects of the pandemic on cocoa exports. in the country. Finally, the results showed that the cocoa sector does not reflect a drop in the international marketing of its product, despite the fact that it faces complications for its production.
La presente investigación analiza la incidencia de la emergencia sanitaria sobre el nivel de exportaciones en el sector cacaotero del país, durante el año 2020 con relación a periodos anteriores, mediante la búsqueda y recolección de información en diferentes fuentes estadísticas del país. Ecuador es considerado uno de los principales exportadores de cacao fino de aroma, por lo cual, posee un buen prestigio y reconocimiento en el mercado internacional. Por otra parte, el Covid-19 afectó a todas las actividades económicas a nivel mundial, por esta razón, a través de una metodología cualitativa se realizó una revisión bibliográfica y análisis de datos, para identificar los efectos de la pandemia sobre las exportaciones de cacao en el país. Finalmente, los resultados evidenciaron que el sector cacaotero no refleja una caída en la comercialización internacional de su producto, pese a que enfrentan complicaciones para su producción.
Keywords: CACAO; COVID-19; EXPORTACIONES